2003
DOI: 10.1590/s0004-282x2003000600015
|View full text |Cite
|
Sign up to set email alerts
|

Determinação de autoanticorpos para antígenos da mielina no soro de pacientes HLA - DQB1*0602 com esclerose múltipla

Abstract: RESUMO -Esclerose múltipla (EM) é doença inflamatória desmielinizante do sistema nervoso central (SNC) de natureza autoimune, mediada por linfócitos Th1. A produção de autoanticorpos séricos para proteína básica da mielina (MBP), proteolipídeo PLP e sequência da glicoproteína de oligodendrócito MOG 92-106, foi determinada em 54 indivíduos saudáveis e 26 pacientes com EM expressando ou não o alelo de suscetibilidade HLA-DQB1*0602. Independentemente da expressão do alelo DQB1*0602, todos os pacientes apresentara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
2
0
3
Order By: Relevance
“…Epidemiological studies showed heterogeneous distribution of the disease in the world and incidence of 0.1% in countries of moderate temperature. In tropical countries, such as Brazil, the disease is rare, but recent data reported high incidence in Caucasian and African-Brazilian subjects 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies showed heterogeneous distribution of the disease in the world and incidence of 0.1% in countries of moderate temperature. In tropical countries, such as Brazil, the disease is rare, but recent data reported high incidence in Caucasian and African-Brazilian subjects 19 .…”
Section: Introductionmentioning
confidence: 99%
“…La Esclerosis Múltiple (EM) es una enfermedad autoinmune con carácter crónico y degenerativo del Sistema Nervioso Central (SNC) que afecta al cerebro y médula espinal (Ng, Miller, Gelinas, & Kent-Braun, 2004;Rampello et al, 2007), provocando la inflamación y desmielinización de la materia blanca (Carvalho et al, 2003). Esta pérdida de mielina dificulta la transmisión neurológica, que causa una reducción o pérdida de función (Klonoff, Clark, Oger, Paty & Li, 1999).…”
Section: Introductionunclassified
“…Epidemiological studies showed heterogeneous distribution of the disease in the world and incidence of 0.1% in countries of moderate temperature. In tropical countries, such as Brazil, the disease is rare, but recent data reported high incidence in Caucasian and African-Brazilian subjects 19 . As to diagnosis, there is evidence of two or more lesions in CNS white matter in imaging exams, preferably within one month of interval between symptoms, in patients aged 15 to 50 years.…”
Section: Introductionmentioning
confidence: 99%